Effects of The Combination of Seluang Fish (Rasbora spp.) and Pasak Bumi (Eurycoma Longifolia Jack) on Systemic Inflammation and Neurotransmitter in Stunting Model Rat (Rattus Novergicus) - Didik Dwi Sanyoto; Hendra Nur'amin; Triawanti Triawanti; Dimas Ikhsan Airlangga; Gastin Gabriel Jangkang (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Stunting causes growth and development issues which are characterized by a systemic inflammatory response and neurotransmitter disorder. The South Kalimantan natural resources i.e. extracts of Pasak Bumi (Eurycoma longifolia Jack) and seluang fish have the potential as a modified therapy for stunting management.Objective: To analyze the effect of Pasak Bumi and seluang fish administration in overcoming systemic inflammation and neurotransmitter disorders in the stunting rats model.Methods: Rats were divided into six group i.e Positive Control (KP): Stunting rats + placebo + standard feed; (P1): stunting rats + 70% EPB 15 mg/kg body weight (BW) + standard feed; (P2): Stunting rats + DHA 1 mg/kg BW + standard feed; (P3): Stunting rats + EPB 15 mg/kg BW + DHA 1 mg/kg BW + standard feed; (P4): Stunting rats + seluang fish; (P5): Stunting rats + EPB 15 mg/kg BW + seluang fish for 5 weeks; Parameters measured were levels of IL-6, TNF-α, and serotonin.Results: There were significant differences in levels of TNF-α (p = 0.000) and serotonin (p = 0.000).Conclusion: The administration of Pasak Bumi extract and seluang fish was able to inhibit systemic inflammation and neurotransmitter dysregulation.